Maternal and neonatal factors associated with perinatal deaths in a South African healthcare institution - Nthabisenu S. Malinga; Antoinette du Preez; Tinda Rabie (AOSIS, 2020)
Background: Research indicated the prevalence of perinatal deaths of infants immediately or up to a week after birth and includes fresh and macerated stillbirths and neonatal deaths. Worldwide, there is a decline in perinatal deaths. However, in South Africa, it is not the case. Often the quality of maternity care is considered as the most important contributing factor for these deaths. However, maternal and neonatal factors can also contribute. Aim: The aim of the study was to determine the maternal and neonatal factors associated with perinatal deaths in a single selected district hospital within the Free State Province of South Africa. Setting: The maternity unit of the largest district hospital in the specific district in the Free State Province of South Africa. Method: A clinical audit design was used. Units of analysis comprised the Perinatal Problem Identification Programme (PPIP) database of neonates born during 2015, and their mothers. A random sample of 384 alive neonates and an all-inclusive sample of 43 deceased neonates were taken from a total of 2319. Descriptive statistics were reported and Cohen's effect sizes, d, were calculated to identify practically significant differences between the neonates in the alive and the deceased group, respectively. Results: Cohen's effect sizes and logistical regression analyses indicate that the Apgar score recorded 10 min after birth, gestational age, birth weight of neonate and the parity of the mother were the most practically significant factors influencing a neonate's chances of survival. Conclusion: Quality maternity care is not the only cause of perinatal mortality rates; maternal and neonatal factors are also contributors.